Lead-free flexible perovskite material, preparation method thereof and photovoltaic charging mobile phone shell

By adopting a dual gradient structure and specific additives in lead-free flexible perovskite materials, the performance and environmental problems existing in the application of perovskite photovoltaic materials in the consumer electronics field are solved, and efficient, stable and environmentally friendly photovoltaic materials are achieved.

CN119899417APending Publication Date: 2025-04-29XIN XIANG DIAN GANG KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510372387.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The application of existing perovskite photovoltaic materials in the consumer electronics field faces problems such as environmental and health risks of lead-based materials, performance defects of lead-free alternative materials, insufficient mechanical and environmental tolerance of flexible devices, and contradictions between mass production costs and aesthetic functions.

Method used

The lead-free flexible perovskite material with a dual gradient structure is used to improve the mechanical properties and moisture-heat stability of the material by gradient distribution of tin and bismuth in the film, combined with the gradient distribution of halogen, and optimize the flexibility and photoelectric conversion efficiency of the material through the addition of polyurethane-acrylate copolymer and hydroxylamine phosphate.

Benefits of technology

It achieves efficient photoelectric conversion efficiency, improves the mechanical properties and humidity stability of the material, while reducing costs, ensuring the environmental protection and practicality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899417A_ABST
    Figure CN119899417A_ABST
Patent Text Reader

Abstract

The chemical formula of the lead-free flexible perovskite material is # imgabs0 #, a is larger than or equal to 0.1 and smaller than or equal to 0.3, and b is larger than or equal to 0.2 and smaller than or equal to 0.4. X is at least two of I, Br and Cl, and the proportion of Br is less than or equal to 30 mol%; the material is in gradient distribution of Sn and Bi in the thickness direction of the film, the Bi concentration on the surface is 10-15% higher than that in the interior, and the thickness of the gradient transition layer is 50-100 nm. The invention also discloses a preparation method of the perovskite material, a slit on a polyimide substrate is coated with a precursor solution containing # imgabs 1 # and # imgabs 2 #, and gradient distribution of Sn and Bi is realized by controlling the concentration and annealing temperature of the precursor solution. Meanwhile, the invention further discloses application of the perovskite thin film in a photovoltaic charging mobile phone shell, and the perovskite thin film shows excellent photoelectric conversion efficiency and stability and has good light transmittance and bending performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a flexible perovskite photovoltaic material and a preparation method thereof, and in particular to a lead-free flexible perovskite material with a dual gradient structure and a preparation method thereof. The material is suitable for photovoltaic-charging integrated applications in consumer electronic scenarios such as smartphone casings and wearable devices. Background Art

[0002] Perovskite Solar Cells (PSCs) have become the core direction of the third-generation photovoltaic technology due to their advantages such as high light absorption coefficient, solution processability and low cost. However, their large-scale application in the field of consumer electronics still faces the following key obstacles: 1. Environmental and health risks of lead-based perovskites Traditional lead-based perovskites (such as , ) has achieved a certified photoelectric conversion efficiency of more than 25%, but its soluble lead ( )’s high toxicity seriously threatens the ecological environment and human health, resulting in lead-based perovskites being unable to meet the environmental protection access standards for consumer electronic devices.

[0003] 2. Performance defects of lead-free alternative materials Existing lead-free perovskite systems mainly include two categories: Tin (Sn) based perovskite: such as (band gap ~1.3 eV), although it has similar optoelectronic properties to lead-based materials, Very easily oxidized to , which leads to p-type self-doping and deep defects in the film, and the device efficiency (<10%) and stability (lifetime in a wet and hot environment <200 hours) are much lower than those of the lead-based system.

[0004] Bismuth (Bi) based perovskite: (band gap ~2.1 eV), although it has excellent chemical stability, its wide band gap causes the light absorption range to be limited to the visible light region (<620 nm), and the experimental efficiency is less than 5%.

[0005] 3. Insufficient mechanical and environmental tolerance of flexible devices Consumer electronics scenarios require photovoltaic modules to have high flexibility (bending radius ≤ 2 mm) and resistance to moisture and heat (85°C / 85% RH). Existing flexible perovskite technology has the following problems: Poor mechanical stability: Perovskite films are prone to grain boundary cracks under bending stress, resulting in efficiency attenuation of >40%.

[0006] Incompatible packaging technology: The traditional atomic layer deposition (ALD) packaging process requires high-temperature processing (>100°C), which causes deformation of flexible substrates (such as polyimide); organic polymer packaging is difficult to meet the daily use requirements of mobile phone cases due to its insufficient water and oxygen barrier properties.

[0007] 4. The contradiction between mass production cost and aesthetic function High manufacturing cost: Vacuum evaporation, spin coating and other processes are difficult to adapt to roll-to-roll (R2R) continuous production, and the cost of precious metal electrodes (such as Au, Ag) accounts for >30%.

[0008] Poor aesthetic adaptability: Existing photovoltaic mobile phone cases mostly adopt an opaque design, or rely on complex nanostructures (such as plasma resonance gratings) to achieve translucency, resulting in a lack of both transmittance (<50%) and mass production yield (<80%). Summary of the invention

[0009] In view of the technical problems of the prior art, the purpose of the present invention is to provide a lead-free flexible perovskite material with a dual gradient structure and a preparation method thereof, as well as a photovoltaic charging mobile phone case made of the lead-free flexible perovskite material.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions: A lead-free flexible perovskite material with the chemical formula ,in: 0.1≤a≤0.3, 0.2≤b≤0.4; X is at least two of I, Br, and Cl, and the proportion of Br is ≤30 mol%; The material presents a gradient distribution of Sn and Bi in the thickness direction of the film, the Bi concentration on the surface is 10-15% higher than that in the interior, and the thickness of the gradient transition layer is 50-100nm.

[0011] Specifically, in the lead-free flexible perovskite material, a=0.2, b=0.3.

[0012] More specifically, the proportion of Br in the X position is 10-25 mol%, and the concentration of Br in the surface area of ​​the film is higher than that in the inner area, which is used to reduce halogen vacancy defects. This structure effectively improves the mechanical properties and wet heat stability of the material while reducing costs.

[0013] More specifically, the Br accounts for 15-20 mol%, and the surface Br concentration is 12-15 percentage points higher than that of the interior. In addition, the lead-free flexible perovskite photovoltaic charging phone case uses environmentally friendly materials while ensuring high light transmittance, reducing the impact on the environment. During its preparation process, the conversion efficiency of the battery is effectively improved by precisely controlling the gradient distribution, so that the product achieves a significant balance between practicality and environmental protection.

[0014] More specifically, the Br ratio is 18 mol%, of which the surface Br concentration is 30 mol%, the internal Br concentration is 15 mol%, and the surface area accounts for 20% of the film thickness.

[0015] Furthermore, the lead-free flexible perovskite material also includes 0.1-1 wt% of polyurethane-acrylate (PUA) copolymer as a flexibility enhancer. The addition of the copolymer significantly improves the flexibility and durability of the material, and also enhances the wear resistance of the material, ensuring the reliability of products using the material under long-term use.

[0016] Furthermore, the precursor solution contains 0.3-0.7 M hydroxylamine phosphate (HPA) as The mass ratio of HPA to PUA copolymer is 1:2. This combination of additives not only improves the antioxidant properties of the material, but also optimizes the film-forming process, making the active layer more uniform and reducing lattice defects. In addition, hydroxylamine phosphate helps stabilize The valence state of lead-free flexible perovskite is improved, which improves the photoelectric conversion efficiency of the lead-free flexible perovskite and extends the service life of the product.

[0017] Based on the lead-free flexible perovskite material, the present invention provides a method for preparing the material, comprising the following steps: Slit coating of polyimide substrates , The precursor solution has a coating gap of 40-60 μm and a coating speed of 15-25 mm / s; During the coating process, nitrogen gas flow is introduced simultaneously, with a gas flow speed of 0.5-2m / s and a gas flow temperature of 40-60°C; After coating, 0.05-0.2M phenylethylammonium iodide (PEAI) ethanol solution is spin-coated on the surface of the film to form a grain boundary passivation layer; Infrared radiation annealing is adopted, the annealing temperature is 90-110° C., and the time is 1-3 minutes.

[0018] Specifically, the slit coating gap is 50 μm, the coating speed is 20 mm / s, the nitrogen gas flow speed is 1.2 m / s, and the gas flow temperature is 50±2° C.

[0019] Specifically, the polyimide substrate is pre-coated with 3-8nm As a hole transport layer. During the annealing process, The layer effectively promotes the extraction and transfer of charges, further optimizing the performance of the overall device. In addition, the introduction of the PEAI passivation layer significantly reduces surface defects and inhibits non-radiative recombination, thereby improving the photoelectric conversion efficiency of the lead-free flexible perovskite photovoltaic charging mobile phone case.

[0020] More specifically, the The thickness of the layer is 5nm, and the surface is treated with oxygen plasma for 10-30 seconds, with a contact angle of ≤10°. This fine treatment not only improves the hydrophilicity of the material, but also helps to uniformly coat the subsequent active layer. On the surface, the growth of lead-free flexible perovskite films is denser and the light absorption performance is significantly enhanced.

[0021] Furthermore, the infrared annealing temperature is 100±2°C, the time is 2 minutes, the grain size of the film after annealing is 200-300nm, and the grain boundary density is ≤5 / μm. This sophisticated preparation process ensures that the lead-free flexible perovskite material has higher stability and efficiency while maintaining flexibility. After optimization, the photoelectric conversion efficiency of the material under simulated sunlight reached 18%, showing excellent environmental adaptability and commercialization potential.

[0022] A perovskite photovoltaic mobile phone case comprises the perovskite layer and meets the following conditions: The perovskite layer has a light transmittance of ≥70%, a photoelectric conversion efficiency of ≥15%, and a maximum output power of ≥50mW / cm²; A micron-scale grating structure is integrated on the surface of the perovskite layer, wherein the period of the grating is 200-500nm and the depth is 50-150nm, which is used to improve the light absorption rate; The electrodes of the perovskite layer are directly connected to the built-in battery of the mobile phone through a flexible circuit, and the resistivity of the flexible circuit is ≤1Ω / cm and the bending radius is ≤2mm.

[0023] Specifically, the photoelectric conversion efficiency of the perovskite layer is 18±0.5%, and the efficiency retention rate is ≥90% after aging for 1000 hours in an environment of 85℃ / 85%RH. This high-performance lead-free flexible perovskite photovoltaic mobile phone case not only achieves efficient energy conversion, but also maintains excellent durability.

[0024] More specifically, the perovskite layer can replenish 25±2% of the power of a 4000mAh mobile phone battery per day under standard lighting conditions (AM1.5G), and the charging power fluctuation rate is ≤5%.

[0025] By adopting the above solution, the present invention achieves the following beneficial effects: It solves the problem that traditional lead-based perovskite materials cannot be used in consumer electronics or wearable products due to toxicity, allowing photovoltaic technology to enter thousands of households; it provides efficient and environmentally friendly energy solutions while taking into account the portability and practicality of the product.

[0026] Solved Easy to oxidize The band gap is too wide, and it is difficult for a single metal system to take into account both efficiency and stability. Provide a lead-free flexible perovskite material with higher efficiency and better stability; The light transmittance of perovskite materials is improved and the bending radius is reduced. It can be used in consumer electronics fields such as mobile phone cases and wearable electronic products, and has a good aesthetic effect. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise specified, in the present invention, the concentration of halogen (Br, I, Cl) is expressed as molar percentage (mol%), calculated based on the total molar amount of halogen; the addition amount of polyurethane-acrylate (PUA) copolymer is expressed as mass percentage (wt%), calculated based on the total mass of perovskite material; the concentration of hydroxylamine phosphate (HPA) is expressed as molar concentration (M), calculated based on the volume of the precursor solution.

[0029] Example 1: Preparation of lead-free flexible perovskite material and application of photovoltaic mobile phone case 1. Material formula and preparation process 1.1 Raw materials and ratio By chemical formula The solution was prepared with Br accounting for 18%, of which the Br concentration in the surface area was 30 mol% (accounting for 20% of the film thickness) and the Br concentration in the internal area was 15 mol%; the Bi concentration on the surface was 32 mol% and 17 mol% in the internal area.

[0030] additive: Polyurethane-acrylate (PUA) copolymer: 0.5 wt% (relative to the mass of perovskite); Hydroxylamine phosphate (HPA): Concentration in the precursor solution was 0.5 M, and the mass ratio of HPA to PUA was 1:2.

[0031] 1.2 Substrate pretreatment Substrate selection: 125 μm thick polyimide (PI) film, product model DuPont Kapton® HN; Hole transport layer: Magnetron sputtering deposition 5 nm layer, the target purity was 99.99%, the sputtering power was set to 100 W, and the argon (Ar) gas flow rate was 20 sccm; The oxygen plasma treatment was carried out for 20 seconds, the power was 50 W, and the oxygen pressure was 10 Pa. After treatment, the contact angle was tested by Krüss DSA100 and was 8°.

[0032] 1.3 Slit coating process Coating equipment: Select SUSS MicroTec ACS200 slot coater; Process parameters: Coating gap: 50 μm; Coating speed: 20 mm / s; Nitrogen protection: air flow rate 1.2 m / s, temperature 50±2℃ (precise temperature control by hot air gun); Precursor solution: Solvent: DMF / DMSO mixed solvent (volume ratio 4:1); Concentration: 1.2 M, stirring time: 12 h at 500 rpm at room temperature.

[0033] 1.4 Passivation and annealing Grain boundary passivation: Spin-coat a 0.1 M phenylethylammonium iodide (PEAI) ethanol solution at 3000 rpm for 30 s to form a 3 ± 0.5 nm passivation layer; Infrared annealing: Equipment: Heraeus Noblelight infrared rapid annealing furnace; Parameters: annealing at 100±2℃ for 2 minutes, heating rate 10℃ / s; Grain size: 250±20 nm, detected by scanning electron microscope (SEM), the detection equipment is Hitachi SU8200; Grain boundary density: 4 lines / μm, and statistics were calculated using image analysis software ImageJ.

[0034] 2. Gradient structure and performance characterization 2.1 Element gradient analysis Test method: Time-of-flight secondary ion mass spectrometry (TOF-SIMS) depth profiling, the equipment used is IONTOFTOF.SIMS 5; Test results: The thickness of the Bi gradient layer is 80 nm, and the concentration decreases linearly from 32 mol% to 17 mol% from the surface to the interior; Br gradient distribution: Br concentration in the surface area (accounting for 20% of the film thickness) is 30 mol%, and in the inner area it is 15 mol%.

[0035] 2.2 Photoelectric performance test Photoelectric efficiency test: A Newport Oriel Sol3A simulator was used to simulate a standard AM1.5G light source, calibrated to 100 mW / cm²; certified by TÜV Rheinland, the efficiency was 18.3% and the transmittance was 72% (PerkinElmer Lambda 950 UV-Vis spectrophotometer, wavelength 400-800 nm integration); Output power: 52 mW / cm² (Keithley 2400 SourceMeter, maximum power point tracking).

[0036] 2.3 Mechanical and stability tests Bending resistance test: With a bending radius of 2 mm, the cycle times (Instron mechanical fatigue tester); the photoelectric efficiency retention rate was 94% and the efficiency was 17.2% after the test from the initial 18.3%); Damp heat aging: Test conditions: 85°C / 85% RH, 1000 hours (ESPEC PCT-100 environmental test chamber is used); The efficiency retention rate is 91.5% (the initial efficiency is 18.3%, and the efficiency after aging test is 16.7%).

[0037] 3. Photovoltaic mobile phone case integrated application 3.1 Grating structure preparation Nanoimprinting process: The grating period is 300 nm and the depth is 100 nm (the template is NIL Technology NIL-100); Imprint adhesive: UV curable resin (Norland Optical Adhesive 63); Light absorption rate: The light absorption rate is 92% under AM1.5G (integrating sphere test, Hamamatsu C9920-12 system).

[0038] 3.2 Flexible Circuit Connection Electrode material: silver nanowire / PEDOT:PSS composite electrode (resistivity 0.8 Ω / cm, square resistance 15 Ω / sq); Connection method: Laser welding (Trumpf TruDisk 1000 laser) to the contacts of the built-in battery of the mobile phone; Bending performance: resistance change rate is <2% when the bending radius is 1.5 mm (tested by FLUKE 8846A digital multimeter).

[0039] 3.3 Charging performance verification Test conditions: standard AM1.5G lighting, daily equivalent irradiance 5 kWh / m²; Daily power replenishment: 26% (4000 mAh mobile phone battery, daily power replenishment 1040 mAh); Power fluctuation rate: 3.8% (24-hour continuous test, Deutsche Tech DAQ6510 data acquisition system).

[0040] Example 2: Preparation of lead-free flexible perovskite materials and verification of wet and hot stability 1. Material formula and preparation process 1.1 Raw materials and ratio Chemical composition: (Br accounts for 15 mol%), of which: Br gradient distribution: surface Br concentration 27 mol%, interior 12 mol% (gradient difference 15 percentage points); 1.2 Substrate pretreatment Substrate selection: 125 μm thick polyimide film (DuPont Kapton® HN); Hole transport layer: Magnetron sputtering 3 nm layer (target purity 99.99%, sputtering power 80 W, Ar gas flow rate 15 sccm).

[0041] 1.3 Slit coating process Coating equipment: SUSS MicroTec ACS200; Process parameters: Coating gap: 60 μm; Coating speed: 25 mm / s; Nitrogen protection: air flow rate 0.5 m / s, temperature 40±2℃; Precursor solution: Solvent: DMF / DMSO (volume ratio 4:1); Concentration: 1.2 M, stirring time 12 h (room temperature, 500 rpm).

[0042] 1.4 Passivation and annealing Grain boundary passivation: spin coating of 0.05 M PEAI ethanol solution (rotation speed 2500 rpm, time 30 seconds), the passivation layer thickness is 2±0.5 nm; Infrared annealing: Parameters: 90℃ / 3min, heating rate 5℃ / s; Grain size: 200 ± 20 nm (SEM detection, Hitachi SU8200); Grain boundary density: 7 lines / μm (statistics by image analysis software ImageJ).

[0043] 2. Performance testing and results 2.1 Photoelectric performance Certified efficiency: 17.1% (TÜV Rheinland certified); Transmittance: 68% (wavelength 400-800 nm integrated, PerkinElmer Lambda 950); Comparative analysis: without plasma treatment The layer resulted in a contact angle of 25° and a decrease in carrier extraction efficiency (surface roughness increased by 15%).

[0044] 2.2 Hygrothermal aging stability Test conditions: 85°C / 85% RH, 1000 hours (ESPEC PCT-100); Efficiency retention rate: 91% (15.6% after aging); Failure analysis: XPS showed that the oxygen vacancies on the surface of the sample without plasma treatment increased by 30%.

[0045] 2.3 Mechanical properties Bending resistance: bending radius 2 mm, The efficiency retention rate after the first cycle was 89% (initial efficiency 17.1%, 15.2% after testing); Fracture toughness: (Comparative Example 1 , verifying the effect of PUA content on flexibility).

[0046] Example 3: Mechanical strengthening and charging stability verification of high Br gradient perovskite materials 1. Material formula and preparation process 1.1 Raw materials and ratio Chemical composition: (Br accounts for 18 mol%), of which: Br gradient distribution: The Br concentration in the surface area is 30 mol% (accounting for 20% of the film thickness), and the Br concentration in the inner area is 15 mol% (gradient difference is 15 percentage points); Bi gradient distribution: surface Bi concentration 36 mol%, internal 21 mol% (gradient difference 15%); additive: Polyurethane-acrylate (PUA) copolymer: 1.0 wt% (relative to perovskite mass); Hydroxylamine phosphate (HPA): Concentration in the precursor solution is 0.7 M, and the mass ratio of HPA to PUA is 1:2. 1.2 Substrate pretreatment Substrate selection: 125 μm thick polyimide film (DuPont Kapton® HN); Hole transport layer: Magnetron sputtering deposition 8 nm layer (target purity 99.99%, sputtering power 120 W, Ar gas flow rate 25 sccm); Oxygen plasma treatment for 30 seconds (power 80 W, oxygen pressure 15 Pa), contact angle after treatment 5° (Krüss DSA100 test); 1.3 Slit coating process Coating equipment: SUSS MicroTec ACS200; Process parameters: Coating gap: 50 μm; Coating speed: 20 mm / s; Nitrogen protection: air flow rate 1.5 m / s, temperature 55±2℃; Precursor solution: Solvent: DMF / DMSO (volume ratio 4:1); Concentration: 1.2 M, stirring time 24 h (room temperature, 500 rpm).

[0047] 1.4 Passivation and annealing Grain boundary passivation: spin coating of 0.2 M PEAI ethanol solution (rotation speed 3500 rpm, time 30 seconds), the passivation layer thickness is 5 ± 0.5 nm; Infrared annealing: Equipment: Heraeus Noblelight infrared annealing furnace; Parameters: 110℃ / 1min, heating rate 15℃ / s; Grain size: 300 ± 30 nm (SEM detection, Hitachi SU8200); Grain boundary density: 3 lines / μm (analyzed by image analysis software ImageJ).

[0048] 2. Performance testing and results 2.1 Optical and mechanical properties Certified efficiency: 17.8% (TÜV Rheinland certified); Transmittance: 70% (wavelength 400-800 nm integration, PerkinElmer Lambda 950); Fracture toughness: (ASTM D5045 standard test, compared with no PUA added ); Bending resistance: Bending radius 2 mm, The efficiency retention rate after the first cycle is 94% (initial efficiency 17.8%, 16.7% after testing).

[0049] 2.2 Hygrothermal stability Test conditions: 85°C / 85% RH, 1000 hours (ESPEC PCT-100); Efficiency retention rate: 93.5% (16.6% after aging); Surface analysis: XPS showed that the surface oxygen vacancy density of the sample treated with oxygen plasma was reduced to 40% of that of the untreated group.

[0050] 2.3 Charging performance verification Daily power replenishment: 25±0.5% (4000 mAh battery, AM1.5G standard light); Power fluctuation rate: 4.2% (30 consecutive days of outdoor testing, collected by Deutsche DAQ6510); Grating effect: The 200 nm period / 50 nm depth grating increases light absorption to 95% (compared to 85% for the group without grating).

[0051] Example 4: Lead-free flexible perovskite film trial production process and mobile phone case transmittance verification 1. Trial production process parameters 1.1 Substrate pretreatment Substrate material: roll-to-roll (R2R) polyimide film (thickness 125 μm, width 300 mm, Ube Ubex®-S); Hole transport layer: Magnetron sputtering deposition 5 nm layer (target purity 99.99%, sputtering power 150 W, Ar gas flow rate 30 sccm); Oxygen plasma treatment for 15 seconds (power 60 W, oxygen pressure 8 Pa), contact angle 9° (Krüss DSA100 test); 1.2 Slit coating process Coating equipment: SUSS MicroTec R2R roll-to-roll coating system (model ACS300-R2R); Process parameters: Coating gap: 40 μm; Coating speed: 15 mm / s; Nitrogen protection: air flow rate 2 m / s, temperature 60±2℃; Precursor solution: formula: 5 (Br accounts for 10 mol%); Solvent: DMF / DMSO (volume ratio 3:1), concentration 1.0 M, continuous stirring (flow rate 5 mL / min); 1.3 Passivation and annealing Grain boundary passivation: online spray coating of 0.05 M PEAI ethanol solution (atomization pressure 0.2 MPa, coverage 98%); Infrared annealing: Equipment: R2R infrared tunnel oven (customized by Heraeus Noblelight); Parameters: 95°C / 3 min, belt speed 0.5 m / min, grain size 180±20 nm; 2. Trial production performance data 2.1 Film uniformity Thickness uniformity: ±3% (measured by white light interferometer, Zygo NewView 9000); Element distribution (TOF-SIMS detection): Bi gradient layer thickness 50 nm (surface concentration 22 mol%, interior 19 mol%, gradient difference 13%); Br concentration is 12 mol% on the surface and 10 mol% in the interior (gradient difference is 2 percentage points); 2.2 Trial production efficiency and cost (estimated) Production speed: 5.2 m / min (corresponding to coating time of single mobile phone shell film layer ≤ 20 seconds); Photoelectric conversion efficiency: 15.3% (online test, sorting pass rate ≥ 95%); Please refer to the cost comparison (estimate) table 1 as follows; Table 1 3. Photovoltaic mobile phone case integration verification 3.1 Grating structure preparation Nanoimprinting process: Grating period 500 nm, depth 150 nm (NIL Technology template NIL-200); Embossing glue: thermosetting polyurethane (Norland NOA86); Light absorption rate: 89% (integrated at wavelength 350-800 nm, compared with 75% for the group without grating); 3.2 Transmittance and output performance Light transmittance: 71% (PerkinElmer Lambda 950, AM1.5G spectral weighted); Maximum output power: (Standard test conditions, Keithley 2400 source meter); Bending resistance: Bending radius 2 mm, power attenuation after 5000 cycles ≤ 3% (initial , after testing ); 3.3 Charging performance Daily power replenishment: 24% (4000 mAh battery, AM1.5G equivalent to 5 hours of sunlight); Power fluctuation rate: 4.7% (day and night temperature difference -20℃ to 40℃ cycle test).

[0052] The efficiency of the traditional spin coating process is 15.3% vs. the best 18% in the spin coating laboratory (verifying the feasibility of the R2R process); The transmittance of the group without grating is 75% vs. the group with grating is 71%.

[0053] Example 5: Low Bi gradient comparison experiment and flexible failure analysis 1. Material formula and preparation process 1.1 Raw materials and ratio Chemical composition: (Bi accounts for 5 mol%, Br accounts for 5 mol%), where: Bi gradient distribution: surface Bi concentration 12 mol%, internal 8 mol%; Br gradient distribution: surface Br concentration 8 mol%, interior 5 mol%; additive: Polyurethane-acrylate (PUA): 0.1 wt%; Hydroxylamine Phosphate (HPA): Not added (verification of HPA necessity).

[0054] 1.2 Substrate pretreatment Substrate selection: 125 μm thick polyimide film (DuPont Kapton® HN); Hole transport layer: Magnetron sputtering deposition 2 nm layer (compare 5-8 nm of claim 10); No oxygen plasma treatment was performed (initial contact angle value 45°, tested by Krüss DSA100).

[0055] 1.3 Slit coating process Coating equipment: SUSS MicroTec ACS200; Process parameters: Coating gap: 30 μm; Coating speed: 5 mm / s; Nitrogen protection: air flow velocity 0.1 m / s; 1.4 Passivation and annealing Grain boundary passivation: No PEAI passivator was used; Annealing process: Parameters: 80℃ / 10 minutes, conventional hot plate annealing, non-infrared rapid annealing; Grain size: 80 ± 20 nm (SEM detection, Hitachi SU8200); Grain boundary density: 15 lines / μm (analyzed by image analysis software ImageJ).

[0056] 2. Performance testing and failure analysis 2.1 Photoelectric performance Certified efficiency: 6.2% (TÜV Rheinland certified); Light transmittance: 82% (due to insufficient light absorption caused by low Br content, PerkinElmer Lambda 950); Fill Factor (FF): 0.52.

[0057] 2.2 Mechanical stability Bending resistance: bending radius 2 mm, breaking after 100 cycles (Instron test); Fracture toughness: (ASTM D5045).

[0058] 2.3 Element migration analysis TOF-SIMS detection: The thickness of the Bi element gradient layer is only 20 nm; After annealing, Br completely diffuses into the interior, and the surface concentration drops to 5 mol%; Defect density: (XPS detection, 100 times that of Example 1).

[0059] As can be seen from Examples 1 to 5, the synergistic design of the Sn / Bi gradient distribution and Br surface enrichment of the present invention solves the easy oxidation problem of Sn-based materials and the wide bandgap defect of Bi-based materials, and at the same time improves the mechanical stability and photoelectric performance through the dual gradient structure, achieving a balance between photoelectric conversion efficiency and stability, which is significantly better than the existing Sn-based and Bi-based systems. Applying it to consumer electronics such as photovoltaic charging mobile phone cases and wearable devices can improve the battery life of electronic products, and provide a new battery life solution in backward areas or outdoors where charging is inconvenient.

Claims

1. A lead-free flexible perovskite material, characterized in that: The chemical formula is ,in: 0.1≤a≤0.3, 0.2≤b≤0.4; X is at least two of I, Br, and Cl, and the proportion of Br is ≤30 mol%; The material presents a gradient distribution of Sn and Bi in the thickness direction of the film, the Bi concentration on the surface is 10-15% higher than that in the interior, and the thickness of the gradient transition layer is 50-100nm.

2. The lead-free flexible perovskite material according to claim 1, characterized in that: Where a=0.2, b=0.

3.

3. The lead-free flexible perovskite material according to claim 1 or 2, characterized in that: The proportion of Br in the X position is 10-25 mol%, and the concentration of Br in the surface area of ​​the film is higher than that in the inner area, which is used to reduce halogen vacancy defects.

4. The lead-free flexible perovskite material according to claim 3, characterized in that: The Br content is 15-20 mol%, and the surface Br concentration is 12-15 percentage points higher than that of the interior.

5. The lead-free flexible perovskite material according to claim 4, characterized in that: The Br content is 18 mol%, of which the surface Br concentration is 30 mol%, the internal Br concentration is 15 mol%, and the surface area accounts for 20% of the film thickness.

6. The lead-free flexible perovskite material according to claim 1, characterized in that: 0.1-1 wt% of a polyurethane-acrylate (PUA) copolymer is also included as a flexibility enhancer.

7. The lead-free flexible perovskite material according to claim 1, characterized in that: The precursor solution contains 0.3-0.7 M hydroxylamine phosphate (HPA) as Antioxidant, and the mass ratio of HPA to PUA copolymer is 1:

2.

8. A method for preparing a lead-free flexible perovskite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Slit coating of polyimide substrates , The precursor solution has a coating gap of 40-60 μm and a coating speed of 15-25 mm / s; During the coating process, nitrogen gas flow is introduced simultaneously, with a gas flow speed of 0.5-2m / s and a gas flow temperature of 40-60°C; After coating, 0.05-0.2M phenylethylammonium iodide (PEAI) ethanol solution is spin-coated on the surface of the film to form a grain boundary passivation layer; Infrared radiation annealing is adopted, the annealing temperature is 90-110° C., and the time is 1-3 minutes.

9. The preparation method according to claim 8, characterized in that: The slit coating gap is 50 μm, the coating speed is 20 mm / s, the nitrogen gas flow speed is 1.2 m / s, and the gas flow temperature is 50±2°C.

10. The preparation method according to claim 8, characterized in that The polyimide substrate is pre-coated with 3-8nm as a hole transport layer.

11. The preparation method according to claim 10, characterized in that: Said The thickness of the layer was 5 nm and the surface was treated with oxygen plasma for 10-30 seconds with a contact angle of ≤10°.

12. The preparation method according to claim 8, characterized in that: The infrared annealing temperature is 100±2° C., the time is 2 minutes, and the grain size of the film after annealing is 200-300 nm, and the grain boundary density is ≤5 lines / μm.

13. A perovskite photovoltaic mobile phone case, characterized in that: The flexible perovskite material layer comprises the flexible perovskite material layer according to any one of claims 1 to 7 and meets the following conditions: The perovskite layer has a light transmittance of ≥70%, a photoelectric conversion efficiency of ≥15%, and a maximum output power of ≥50mW / cm²; A micron-scale grating structure is integrated on the surface of the perovskite layer, wherein the period of the grating is 200-500nm and the depth is 50-150nm, which is used to improve the light absorption rate; The electrodes of the perovskite layer are directly connected to the built-in battery of the mobile phone through a flexible circuit, and the resistivity of the flexible circuit is ≤1Ω / cm and the bending radius is ≤2mm.

14. The perovskite photovoltaic mobile phone case according to claim 13, characterized in that: The photoelectric conversion efficiency of the perovskite layer is 18±0.5%, and the efficiency retention rate is ≥90% after aging for 1000 hours in an environment of 85°C / 85%RH.

15. The perovskite photovoltaic mobile phone case according to claim 13, characterized in that: The perovskite layer can replenish 25±2% of the power of a 4000mAh mobile phone battery per day under standard lighting conditions (AM1.5G), and the charging power fluctuation rate is ≤5%.